Single crystal x-ray analysis of 2,3-benzylidene-1,6-anhydro-B-D-mannopyranoside - Pangan, Lourdes N. (Animo Repository, 1997)
The structure of 2,3-benzylidene-1,6-anhydro-B-D-mannopyranoside (C13H14O5), an intermediate in the preparationof a macrocycle containing B-D-mannose and tetrathiafulvalene units, was determined from single crystal X-ray diffraction and refinement. The molecule had crystallized in a monoclinic P21 space group and a unit cell dimensions and a=6.3308(4) A,b=7.0622(8)A,c=13.0160(8)A,B=96.417(4)',V=578.29 A3,Z=2,Dc=1.437 g cm-3 and u (MoKa)=0.11 mm-1. The crystal structure was solved by direct methods with 1292 observed reflections. Refinement by least squares methods gave a final wR2 factor of 0.0699 and a final R factor of 0.0246. The molecules in the lattice are stacked along the b-axis and are held by strong H-bonding forces with intermolecular close contact (O-H...O) = 1.996(5) A. All crystallographic measurements were made using a Siemens P4 single crystal X-ray diffractometer.